Two step sintering process and metal grid design optimization for highly efficient ITO free organic photovoltaics - Neophytou, Marios; Georgiou, Efthymios; Fyrillas, Marios M.; Choulis, Stelios A. (My University, 2014)
The need for inexpensive alternative to indium doped tin oxide (ITO) transparent electrodes is imminent for cost-efficient solution processed optoelectronic applications. ITO-free transparent electrodes can be based on inkjet-printed Silver (Ag) nanoparticles grids embedded into PEDOT:PSS buffer layers. We present an in-depth investigation of the morphological evolution of the inkjet printed Ag nanopartricle sintering process combined with an ultimate control of the printed grid design requirements for efficient ITO-free organic photovoltaics (OPVs). We report on glass/ITO-free P3HT:PC60BM and Si-PCPDTBT:PC70BM based OPVs with power conversion efficiency of 2.8% and 4.9% respectively. These devices exhibited minimal losses when compared to reference ITO-based OPVs.
Keywords: Inkjet printing; ITO-Free electrodes; Metal grids; Printed electronics; Silver nanoparticles; Transparent electrodes